2005
DOI: 10.1007/s10517-005-0229-y
|View full text |Cite
|
Sign up to set email alerts
|

Cell therapy of brain stroke

Abstract: Cell suspension consisting of cells from immature nervous and hemopoietic tissues was subarachnoidally transplanted to 10 patients with brain stroke consequences. Clinical effect of different degree was attained in all patients. Six months after cell therapy functional activity significantly increased in contrast to clinically comparable control group. No serious complications of cell therapy were observed. Presumably, cell therapy is a more or less safe method of treatment, which can be effectively used in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 4 publications
(4 reference statements)
0
57
1
Order By: Relevance
“…Promising results from preclinical studies and clinical trials have already been described in several diseases, such as diabetes mellitus [102,103], chronic myeloid leukemia [104,105], cirrhosis [106,107], pulmonary fibrosis [108,109], Crohn’s disease [110,111], heart failure [66,112], and disorders of the nervous system [113,114,115,116,117], and the immunomodulatory effects of stem cells have found their utility in several conditions characterized by predominant inflammation [118,119]. …”
Section: Stem Cells In Clinical Practice and Regenerative Medicinementioning
confidence: 99%
“…Promising results from preclinical studies and clinical trials have already been described in several diseases, such as diabetes mellitus [102,103], chronic myeloid leukemia [104,105], cirrhosis [106,107], pulmonary fibrosis [108,109], Crohn’s disease [110,111], heart failure [66,112], and disorders of the nervous system [113,114,115,116,117], and the immunomodulatory effects of stem cells have found their utility in several conditions characterized by predominant inflammation [118,119]. …”
Section: Stem Cells In Clinical Practice and Regenerative Medicinementioning
confidence: 99%
“…The only trial reporting the use of intrathecal route for cell delivery is that of Reabinovich et al (2005) who used a poorly identified cell population consisting of a mixture of immature nervous and hemopoeitic cells (37).…”
Section: Discussionmentioning
confidence: 99%
“…Rabinovich et al [80] reported on a case-series, nonrandomized, open-label study that included three patients with hemorrhagic strokes in the middle cerebral artery (MCA) territory and seven patients with ischemic strokes in the MCA territory, with or without additional involvement of the anterior cerebral artery (ACA) territory. Subarachnoidal injections of 2 · 10 8 human fetal cells were made between 4 and 24 months after the disease onset.…”
Section: Human Fetal Cellsmentioning
confidence: 99%